Studi Keanekaragaman Lumut (Bryophyta) Di Kawasan Hutan Desa Taupe, Kecamatan Mamasa, Kabupaten Mamasa, Sulawesi Barat - Matias Eman; Arlinda Puspita Sari; Ariandi Ariandi (Jurnal Pendidikan Biologi Undiksha, 2022)
Moss is a plant in the Bryophyta division that has many benefits, especially for the ecosystem. Research on moss diversity has not been widely carried out in the Sulawesi area, especially West Sulawesi. The aim of this study was to determine the diversity of mosses in the forest area of Taupe Village, Mamasa District, Mamasa Regency, West Sulawesi. The sampling was carried out by the cruised method. After that, samples was identified and collected in the form of a herbarium. The research location was divided into 3 stations based on topographic conditions. The results showed that there were 26 species of mosses belonging to 19 families, including: Andreaeaceae, Aneuraceae, Bartramiaceae, Brachytheciaceae, Bryaceae, Dicranaceae, Hookeriaceae, Hypnodendraceae, Jungermaniaceae, Lejeunaceae, Lepidoziaceae, Marchantiaceae, Notothyladaceae, Plagiochilaceae, Pleuroziaceae, Porellaceae, Scapaniaceae, Sematophyllaceae, and Sphagnaceae. The diversity analysis showed that mosses in the Taupe Village Forest had high diversity (H'=3,088), high evenness (E=0,948), low dominance (C=0,051), and medium species richness (R1=4,402).